EFFECTS OF AMLODIPINE BESYLATE ON SPERMATOGENESIS IN SPRAGUE DAWLEY RATS: Effects of Amlodipine Besylate on Spermatogensis - Latif, Rabia; Aslam, Muhammad; Hussain, M Mazhar; Butt, Idrees Farooq; Mubarik, Azhar; Zubair, Alia (Pakistan Armed Forces Medical Journal, 2009)
Objective: To determine the effects of chronic treatment with amlodipine besylate on spermatogenesis in Sprague Dawley rats. Study Design: Quasi experimental study. Place and Duration of Study: The study carried out in the department of Physiology, Army Medical College Rawalpindi in collaboration with the department of Pathology, Army Medical College and National Institute of Health, Islamabad during April 2007 and March 2008. Material and Methods: Thirty male Sprague Dawley rats were divided into two groups; each comprising of 15 rats. Group A was given vehicle whereas group B was given amlodipine besylate (norvasc) by oral and gavage for 50 days along with standard rat diet. Testes were removed 24 h after the last experimental day and sectioned. The sections were stained by hematoxylin and eosin and examined microscopically. Results were analyzed on SPSS version 13. Results: There were significant differences in mean tubular diameter and height of germinal epithelium of testes between amlodipine and vehicle treated rats. Conclusion: Long term treatment with amlodipine besylate (norvasc) results in suppression of spermatogenesis in male rats.